2012
DOI: 10.1002/ange.201206416
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme‐Responsive Controlled Release of Covalently Bound Prodrug from Functional Mesoporous Silica Nanospheres

Abstract: Enzymvermittelte Freisetzung: Die Funktionalisierung von mesoporösen SiO2‐Nanopartikeln mit Sulfasalazin (SZ), einem Prodrug der 5‐Aminosalicylsäure (5‐ASA; siehe Schema) und von Sulfapyridin, ergibt enzymresponsive Nanotransporter. In Gegenwart des Kolon‐spezifischen Enzyms Azo‐Reduktase (orange) werden 5‐ASA und Sulfapyridin effizient freigesetzt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
40
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 53 publications
0
40
0
Order By: Relevance
“…As a late endosomal and lysosomal protease that can specifically hydrolyze Gly-Phe-Leu-Gly (GFLG) sequence, cathepsin B is overexpressed in various types of tumors. 107,108 Cheng et al 109 reported an MSN-based cathepsin-B responsive DDS. As described in Figure 8, the classic rotaxane structure formed with alkoxysilane tether and α-CD was employed to anchor onto the orifices of MSN to serve as gatekeeper and further modified with multi-functional peptide azido-GFLGR7RGDS …”
mentioning
confidence: 99%
“…As a late endosomal and lysosomal protease that can specifically hydrolyze Gly-Phe-Leu-Gly (GFLG) sequence, cathepsin B is overexpressed in various types of tumors. 107,108 Cheng et al 109 reported an MSN-based cathepsin-B responsive DDS. As described in Figure 8, the classic rotaxane structure formed with alkoxysilane tether and α-CD was employed to anchor onto the orifices of MSN to serve as gatekeeper and further modified with multi-functional peptide azido-GFLGR7RGDS …”
mentioning
confidence: 99%
“…And the enzyme-responsive release mechanism could be attributed to the degradation of azo bonds in HMSS-N=N-CS by enzyme, causing the detachment of CS from the surface of HMSS and the fast release from HMSS. Since azo bonds have been reported to be cleaved by enzymes secreted by colonic microflora [35,36].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, when a co-condensation method is used, the pore size of the material is not influenced significantly by the organic functionalities. [8,24,41] Therefore, the azide-functionalized PMOs were synthesized by a one-pot cocondensation method by using BTME and AzPTMS as precursors, as shown in Scheme 1. By using P123 as the template and KCl as an inorganic salt additive, it is possible to obtain materials with a high degree of mesostructural order, large specific surface areas, narrow pore-size distributions, relatively uniform distribution, and tunable content of the azide groups.…”
Section: Resultsmentioning
confidence: 99%